The P‐Word: Power aversion and responsibility aversion as explanations for the avoidance of power. Issue 3 (12th February 2022) - Hull, Kathryn E.; Overbeck, Jennifer R.; Smillie, Luke D.; Howe, Piers D. L.
Abstract: Though we typically think that power is desirable, individuals will sometimes avoid power. One explanation for this behavior is some individuals are averse to the responsibility associated with power and will therefore avoid positions of power. However, people may also avoid power because they perceive it as being inherently negative. This is supported by research on lay theories of power, which suggests that those who endorse the coercive lay theory perceive powerful people as manipulative and deceitful. In this paper, we propose a new theory of power aversion that expands upon the coercive lay theory to more thoroughly explain how negative perceptions of power cause some individuals to avoid it. We draw from previous research to identify specific negative traits associated with power. Based on this, we propose that some power‐averse individuals believe that possessing power will turn them into immoral, cold, selfish, and unjust people. For this reason, they avoid power. We also consider the relationship between power aversion and responsibility aversion and suggest a convergence between research on responsibility aversion and lay theories of power.